The Effectiveness of Human Resource Management (HRM) Strategies on the Performance of Medical Records Staff at the Regional General Hospital of Central Buton Regency, Southeast Sulawesi Province - Anna Maria Daud; Andi Mu’tiah Sari; Shulystiawaty Desy Resky; Sulfianti Fakhruddin (Poltekkes Kemenkes Tasikmalaya, 2026)
Human Resource Management (HRM) plays a significant role in improving the productivity of healthcare workers, including medical records officers in hospitals. Optimal performance by medical records personnel is crucial to ensuring quality healthcare services. However, in its implementation, many obstacles remain that hinder the effectiveness of HRM strategies. This study aims to assess the effectiveness of HRM strategies in improving the performance of medical records personnel at the Buton Tengah District General Hospital in Southeast Sulawesi Province. The method used in this study was a qualitative approach with a descriptive analytical design. Data were collected through observation, interviews, and documentation techniques, with the subjects involved being medical records personnel and hospital management. For data analysis, a content analysis method was used. The results of this study indicate that HRM strategies are not fully effective. Some of the main problems identified are a shortage of personnel, a limited budget, inadequate facilities and equipment, suboptimal implementation of SOPs, and lack of maintenance of existing equipment. The conclusion of this study is that HRM strategies have not been well integrated in efforts to improve the performance of medical records personnel. Therefore, improvements are needed in terms of human resource planning, training, reward systems, and improvements to supporting facilities and infrastructure.